Adaptable Bandwidth for Harmonic Step-Frequency Radar - Anthony F. Martone; Kyle A. Gallagher; Kelly D. Sherbondy; Kenneth I. Ranney; Traian V. Dogaru; Gregory J. Mazzaro; Ram M. Narayanan (International Journal of Antennas and Propagation)
A spectrum sensing technique is described which is used to enhance the performance of harmonic step-frequency radar in the presence of harmful radio frequency (RF) interference (RFI). This technique passively monitors the RF spectrum for subbands of high signal-to-interference-plus-noise ratio (SINR) within a constrained bandwidth of interest. An optimal subband is selected for the harmonic radar that maximizes SINR and minimizes the range resolution cell size, two conflicting objectives. The approach is tested using an experimental setup that injects high power RFI into a harmonic step-frequency radar, which significantly degrades radar performance. It is shown that the proposed spectrum sensing technique significantly improves the SINR and the peak-to-average sidelobe power level of the harmonic radar at the sacrifice of range resolution.